Twentieth Century Regional Climate Change During the Summer in the Central United States Attributed to Agricultural Intensification - Ross E. Alter; Hunter C. Douglas; Jonathan M. Winter; Elfatih A. B. Eltahir (Geophysical Research Letters)
Abstract Both land use changes and greenhouse gas (GHG) emissions have significantly modified regional climate over the last century. In the central United States, for example, observational data indicate that rainfall increased, surface air temperature decreased, and surface humidity increased during the summer over the course of the twentieth century concurrently with increases in both agricultural production and global GHG emissions. However, the relative contributions of each of these forcings to the observed regional changes remain unclear. Results of both regional climate model simulations and observational analyses suggest that much of the observed rainfall increase—as well as the decrease in temperature and increase in humidity—is attributable to agricultural intensification in the central United States, with natural variability and GHG emissions playing secondary roles. Thus, we conclude that twentieth century land use changes contributed more to forcing observed regional climate change during the summer in the central United States than increasing GHG emissions.